Seed storage-mediated dormancy alleviation in Fabaceae from campo rupestre - Nativel, Naïla; Buisson, Elise; Silveira, Fernando Augusto Oliveira (Acta Botânica Brasílica, 2015)
We studied the effects of seed storage on germination and dormancy alleviation in three species of Fabaceae endemic to campo rupestre in southeastern Brazil. Fresh seeds of Collaea cipoensis, Mimosa maguirei and Mimosa foliolosa were set to germinate and germination of seeds after four, five and 13 years of storage was tested. Seed viability was maintained for all species after the full storage period. Seed storage significantly increased germination percentage and decreased germination time for C. cipoensis and M. foliolosa, suggesting the alleviation of physical dormancy with storage. However, we did not find evidence of dormancy alleviation in M. maguirei since stored seeds showed a decrease in germination in comparison to that of fresh seeds. Our data indicate species-specific storage-mediated dormancy alleviation, which will have important implications for restoration of campo rupestre.